White Guerrillas: Transnational Anti-Communism and Right-Wing Imaginaries in Argentina and Mexico, 1954-1972 (Quinto Sol, 2015)
This article explores the “contact zones” between extreme right-wing militant groups in Argentina and Mexico, in terms of their shared intellectual and ideological trajectories, their discourses about “the enemy” (communism) and how they inscribed themselves within particular contexts of conflict during the Cold War. From a comparative perspective, the article deals with the political imaginaries and forms of political action that allowed the Tacuara groups in Argentina, and University Movement of Reformist Orientation (MURO) in México, to play a role in the anticommunist crusades in their respective countries and in Latin America, between 1954 and 1972. Framed by their own particular battles, aspirations and contradictions, these political entities appeared as spaces for nationalist and counterrevolutionary militancy and action, branded by their national particularities, but also as symptoms of a novel conception of political and spiritual struggle against communism at a global scale.
Keywords: anticommunism; nationalism; Cold War; Argentina; Mexico